A sustainable reuse strategy of converting waste activated sludge into biochar for contaminants removal from water: Modifications, applications and perspectives - Hu, Jinwen; Zhao, Ling; Luo, Jinming; Gong, Huabo; Zhu, Nanwen (Journal of hazardous materials, 2022)
Conversion of sewage sludge to biochar for contaminants removal from water achieves the dual purpose of solid waste reuse and pollution elimination, in line with the concept of circular economy and carbon neutrality. However, the current understanding of sludge-derived biochar (SDB) for wastewater treatment is still limited, with a lack of summary regarding the effect of modification on the mechanism of SDB adsorption/catalytic removal aqueous contaminants. To advance knowledge in this aspect, this paper systematically reviews the recent studies on the use of (modified) SDB as adsorbents and in persulfate-based advanced oxidation processes (PS-AOPs) as catalysts for the contaminants removal from water over the past five years. Unmodified SDB not only exhibits stronger cation exchange and surface precipitation for heavy metals due to its nitrogen/mineral-rich properties, but also can provide abundant catalytic active sites for PS. An emphatic summary of how certain adsorption removal mechanisms of SDB or its catalytic performance in PS-AOPs can be enhanced by targeted regulation/modification such as increasing the specific surface area, functional groups, graphitization degree, N-doping or transition metal loading is presented. The interference of inorganic ions/natural organic matter is one of the unavoidable challenges that SDB is used for adsorption/catalytic removal of contaminants in real wastewater. Finally, this paper presents the future perspectives of SDB in the field of wastewater treatment. This review can contribute forefront knowledge and new ideas for advancing sludge treatment toward sustainable green circular economy. [Display omitted] •Various modification methods of sludge-derived biochar (SDB) are introduced.•Explained the mechanism of SDB for adsorption of pollutants/activation of persulfate.•Strategies to enhance the adsorption/catalytic performance of SDB are summarized.•Challenges and further studies for SDB applied to wastewater treatment are presented.